Affilate Practices Through Youtube Streamers In Product Promotion On The @set1awanade Channel - Reizal Rizki; Khaerudin Imawan (Indonesian Journal Publisher, 2026)
This study examines the formation of affiliate practices through social interactions in YouTube live streaming, focusing on the @set1awanade channel. Grounded in Pierre Levy’s New Media Theory, this research aims to identify the forms of social interaction that underlie organic affiliate practices and to analyze how social integration is constructed among streamers, audiences, and brands. A descriptive qualitative approach was employed, using content analysis of live streaming recordings and in-depth interviews with three selected informants who have engaged in purchasing based on the streamer’s recommendations. The findings reveal that affiliate practices emerge organically through three main interaction patterns: (1) audience-initiated communication via the Saweria donation platform, which allows viewers to influence discussion topics; (2) the internalization of the attention economy as a social ritual, where donation value determines message visibility and response priority; and (3) the development of authenticity through parasocial closeness, fostering trust between the streamer and audience. Furthermore, social integration is formed through dynamic interactions in the live chat, the use of community-specific symbolic language, and the streamer’s role as a validator who legitimizes product recommendations. This study concludes that in the new media environment, social interaction and integration function as the primary foundation enabling the emergence of affiliate practices. Economic actions, such as purchasing through affiliate links, are preceded and strengthened by social processes within the digital community. These findings highlight the importance of community-based engagement in developing sustainable and effective digital marketing strategies, this study also offers practical implications for content creators and digital marketing practitioners.